2021
DOI: 10.3390/ijms22094333
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin ETB Receptor-Mediated Astrocytic Activation: Pathological Roles in Brain Disorders

Abstract: In brain disorders, reactive astrocytes, which are characterized by hypertrophy of the cell body and proliferative properties, are commonly observed. As reactive astrocytes are involved in the pathogenesis of several brain disorders, the control of astrocytic function has been proposed as a therapeutic strategy, and target molecules to effectively control astrocytic functions have been investigated. The production of brain endothelin-1 (ET-1), which increases in brain disorders, is involved in the pathophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 124 publications
0
17
0
Order By: Relevance
“…The expression of cyclin D1 can be observed in reactive astrocytes after cerebral ischemia ( Di Giovanni et al, 2005 ; Zhu et al, 2007 ). Interestingly, some studies have found that endothelin-1 (ET-1) can also induce astrocyte activation after brain injury ( Koyama and Michinaga, 2012 ; Koyama, 2021 ). After the intervention with ET-1, the phosphorylation of SP1 and the activity of Cyclin D1 were increased.…”
Section: The Changes Of Astrocytes After Ischemiamentioning
confidence: 99%
“…The expression of cyclin D1 can be observed in reactive astrocytes after cerebral ischemia ( Di Giovanni et al, 2005 ; Zhu et al, 2007 ). Interestingly, some studies have found that endothelin-1 (ET-1) can also induce astrocyte activation after brain injury ( Koyama and Michinaga, 2012 ; Koyama, 2021 ). After the intervention with ET-1, the phosphorylation of SP1 and the activity of Cyclin D1 were increased.…”
Section: The Changes Of Astrocytes After Ischemiamentioning
confidence: 99%
“…Besides this, Off signals from neurons appear important in maintaining tissue homeostasis and limiting microglia activity under inflammatory conditions, presumably preventing damage to intact parts of the brain [ 143 ]. Endothelin B-receptor-mediated regulation of astrocytic activation was reported to improve brain disorders, such as neuropathic pain [ 144 ]. SP also directly activates microglia and astrocytes and contributes to microglial activation [ 145 , 146 ], initiating signaling via the nuclear factor kappa B pathway, leading to pro-inflammatory cytokines production [ 147 ] ( Figure 2 E).…”
Section: Neurogenic Inflammationmentioning
confidence: 99%
“…The involvement of the serotonergic Animal studies are one of the most important arenas for pain research. The endothelin receptor mediates the alteration of astrocyte functions, leading to the alleviation of neuropathic pain [124]. The dissociative anesthetics ketamine induces analgesic effects in models of acute pain and relieves thermal and mechanical allodynia in a chronic neuropathic pain model [125].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%